Enhanced pregnancy outcomes with intrauterine platelet-rich plasma infusion in women following failed personalized embryo transfer guided by endometrial receptivity assay - Kaul, Nalini; Sharma, Meenu; Pathak, Snigdha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Altered endometrial receptivity is an important cause of implantation failure. The embryo-endometrial asynchrony due to ovarian stimulation in IVF cycles contributes to low success rates. Frozen embryo transfer (FET) has become popular a method to overcome this asynchrony. Endometrial receptivity array (ERA) is a molecular test that differentiates a receptive from a non-receptive endometrium. Studies suggest that a personalised embryo transfer (pET) guided by ERA in FET cycles, improves pregnancy rates in recurrent implantation failure (RIF) patients. Despite pET not all patients achieve implantation. Intrauterine infusion of platelet-rich plasma (IUPRP) is emerging as an innovative technique to enhance fertility outcomes in patients with impaired endometrial receptivity. Platelet rich plasma (PRP) contains an abundance of growth factors and cytokines thought to enhance endometrial growth and receptivity. Aim of the study was to evaluate the role of IUPRP in improving pregnancy rate in patients with failed pET. Methods: 53 patients with two previous pET failures, having an endometrial thickness ≥7 mm were included in this observational cohort study. FET was planned in a hormone replacement cycle. 0.4 ml PRP prepared by double centrifugation technique was infused into the uterus on the day of starting progesterone. Results: A pregnancy rate of 64.1% and Live birth rate of 49.06% was achieved at FET after IUPRP infusion. Miscarriage rate was 17.6%. These results are similar to pregnancy and live birth rates achieved in our non-RIF IVF patients. Conclusions: Our study suggests an improved reproductive outcome with infusion of IUPRP in patients with who failed to implant after pET.